Representações sociais da depressão construídas por idosos e suas relações com a capacidade funcional - Veloso, Laura de Sousa Gomes (2017)
Current researches indicate that, every year, around 650,000 people over 60 are entering Brazilian society, most of them with chronic diseases and functional limitations. Among the chronic pathologies, depression stands out, further increasing the cycle of fragility and progressive deterioration of functional capacity. Therefore, the present study aims to verify the social representations built by the elders on depression in old age and its relation with functional capacity, as well as to investigate the association between depressive symptoms and functional capacity. This is an exploratory study, with mixed approach, and secondary database, which included 234 people over 60 years old, of both sexes, assisted by the health teams of the Family Health Strategy Grotão I, II and III, and the Maria de Nazaré Community, in the municipality of João Pessoa, Paraíba, Brazil. The data were collected in the respective health units, through a semi-structured interview, composed by three parts, the first being the Free Word Association Test (TALP), with the inductor term <depression>; followed by sociodemographic characterization; the last part was contemplated by the Geriatric Depression Scale (GDS-15) and functional performance analysis, using the Katz Index and the Lawton and Brody Scale. The data collected were processed by the software SPSS version 21.0 and IRaMuTeQ and later interpreted according to the theoretical contribution of the Social Representations. The results show that 38% (n=88) of the elderly participants presented symptoms suggestive of depression, prevalent among women, in the age group between 60 and 69 years. Moreover, a significant portion of the population (43.6%) were identified as independent persons with no symptoms of depression, although 13.7% self-classified as independent by the Katz index and partially dependent on the Lawton scale. Furthermore, 9.83% of participants with depressive symptoms already showed functional losses for more complex activities, which require associated cognitive and motor skills, as observed in the Instrumental Activities of Daily Living. The analysis of the textual corpus referring to the social representations of depression resulted in the formation of four semantic classes, with use of 77.68%, presented by the Descending Hierarchical Classification (CHD): class 1 - Senses and experiences associated with depression; Class 2 - Aspects related to depression; Class 3 - Clinical aspects of depression; Class 4 - Psychoaffective dimensions of depression. The elders considered functionally dependent represent depression as a serious pathological process of psychoaffective repercussion, which requires clinical and medication assistance, but that care becomes more extended and effective with the presence of family and friends. Data from the present study correlate with each other, and indicate that the presence of depressive symptoms is significantly associated with the progressive decline of Instrumental Activities of Daily Living, as well as with the progressive loss of cognitive performance, suggesting updates to health professionals through practices and orientations directed to the elders, with and without depressive symptoms.